ANALISIS NILAI-NILAI RELIGIUS DALAM FILM CINTA LAKI-LAKI BIASA YANG DIADAPTASI DARI NOVEL KARYA ASMA NADIA - Hadni Imayanti; Mustika Fitri Awaliyah; Agus Priyanto (IKIP Siliwangi, 2018)
The research based on the religion value in the movie of “Cinta Laki-laki Biasa” director by Guntur Soeharjanto that was produced by Starvision adapted from Asma Nadia novel. The writers analyzed the religion value from each part that was told in thet movie. This research aimed to describe the religion value in that movie. The reason why the writers took “Cinta Laki-laki Biasa”, because that movie had a lot of religion values. Beside that, every dialog contained the speech where the viewers can catch the value. This research was very important and useful for the reader, because many moral messages can we get. The writers used bilbliography research as the research method. The result from the research was the patience feeling, simplicity, alwasy pray to God even though have a lot of businesses, have a good attitude, helping each other, respecting parent, sincere, and never give up. The religion value can be applied in human daily life.